Biodegradable multifunctional additives for lube oil: Synthesis and characterization. (17th July 2016) - Upadhyay, M.; Dey, K.; Ghosh, P.
ABSTRACT: Homopolymers of isodecyl acrylate and isooctyl acrylate and copolymers of each of them with β-pinene (BP) were synthesized and characterized by spectral, thermogravimetric, and gel permeation chromatographic analysis. Pour point depressant (PPD) and viscosity index improver (VII) properties were tested with additive-doped base oil in terms of pour point (PP) and viscosity index (VI), respectively. Although the isodecyl acrylate polymers were thermally more stable than the isooctyl acrylate polymers, the latter showed higher VI and PPD efficiency. VI and PP values of the additive-doped base oils depend on the nature of mineral base oils as well as on the type and concentration of VII. In addition, introduction of BP moiety in the acrylate backbone has induces excellent biodegradability in the above polymers.